The Terwilliger algebra of symplectic dual polar graphs, the subspace lattices and U(sl2) - Bernard, Pierre-Antoine; Crampé, Nicolas; Vinet, Luc (Discrete mathematics, 2022)
The adjacency matrix of a symplectic dual polar graph restricted to the eigenspaces of an abelian automorphism subgroup is shown to act as the adjacency matrix of a weighted subspace lattice. The connection between the latter and Uq(sl2) is used to find the irreducible components of the standard module of the Terwilliger algebra of symplectic dual polar graphs. The multiplicities of the isomorphic submodules are given.